The Child’s World of the Tuvan Riddle: A Linguocultural Analysis - Bochina, Tatyana G.; Lomakina, Olga V. (The New Research of Tuva, 2026)
Riddles, like other paremiological texts, represent features of a linguoculture, including its axiosphere, in which children occupy an important place and are construed as a value. The aim of the article is to identify the linguocultural features of Tuvan riddles about children and baby animals. The primary source of the study is G. N. Kurbatsky’s collection of Tuvan riddles (2021), comprising 1,121 items. The objects of analysis are both denotata (solutions) and significata (encoding texts) of riddles containing the component “children”. Tuvan riddles that include a component naming a child or designating an animal young exhibit both shared and specific features. The similarity lies in the use of images of both children and baby animals to convey an ethnically marked model of the family (clan). This model is supported by the unity of its members, each of whom is distinctive and performs a particular function. In the encoding part of the riddle, the child metaphor is explicated through a feature common to both the enigma and the enigmatizing element. This may be either the parametric feature “small” or a processual feature. Both groups of riddles are characterized by ethnocultural connotation in both the encoding and encoded parts of the enigmatical text, as well as by the enrichment of the metaphorical code through specific everyday realities, traditions, and rituals. Differences are manifested in that nominations of a child are used in both parts of the enigmatical text, whereas names of baby animals occur only in the proper riddle text. The differentiation of animals by age is reflected in the presence of different lexical items in the language for the same animal depending on its age status. However, this knowledge is transmitted to the addressee of the riddle only in the descriptive part of the paremia and does not constitute its theme. The interaction of various cultural codes in Tuvan riddles about children (anthroponymic, zoonymic, and object-related) has also been established.